Transcutaneous electrical nerve stimulation in the management of calf muscle spasticity in cerebral palsy - Logosu, D.; Tagoe, T.A.; Adjei, P. (IBRO Neuroscience Reports, 2021)
This study sets out to evaluate the effectiveness of transcutaneous electrical nerve stimulation (TENS) in the management of calf muscle spasticity in children with cerebral palsy. The study follows a one group pre-test–post- test design involving fifteen children with spastic cerebral palsy, presenting with calf muscle spasticity. Spasticity was assessed before and after a 30 min application of TENS to the bilateral calf muscles. The H-reflex (electromyography) of the calf muscles and Modified Ashworth Scale (MAS) served as a measure of spasticity. A goniometer was used to measure the range of motion (ROM) angles for ankle dorsiflexion. We report here no significant difference (p > 0.05) between the left and right H-reflex responses, MAS scores, and ROM scores recorded at baseline (pre-test). Correlation analysis show no correlation (p > 0.05) between the pre-test HA Max (maximum H-reflex amplitude)/MA Max (maximum M-Wave Amplitude) ratio and MAS scores of both the left and right calf muscles. However, TENS significantly reduced (p < 0.05) the HA of the left calf muscle and MAS scores of the left and right calf muscles. Additionally, TENS significantly increased the ROM scores of the left and right calf muscles. Our findings lend support to existing evidence that TENS is effective in reducing spasticity. The potential mechanism underlying this effect is a reduction in neuron excitability.
A pilot study
Research Article
Keywords: Cerebral palsy; H-reflex; Modified Ashworth Scale; Range of motion; Spasticity; Transcutaneous electrical nerve stimulation